Textile economies : power and value from the local to the transnational - Little, Walter E., 1963-; McAnany, Patricia Ann (Society for Economic Anthropology monographs ;, 2011)
The economy of textiles provides insight into the fabric of social relations, local and global politics, and diverse ideologies. Textile production and exchange represent a key node for the intersections of multiple aspects of ancient and modern economies, including social-class relations, gender, tourism, exchange, commerce, and transpolity relationships. A political economy of textiles, d.